An Attempt to Reduce Nitrogen Fertilization Levels and Their Impact on the Growth and Productivity of Garlic (Allium sativum L.) Under Different Planting Dates - Noura Mohamed Taha; Najat Abdulwahab Bukhari; Ashraf Atef Hatamleh; Krzysztof Górnik; Saleh Shehab Sabah; Fadl Abdelhamid Hashem; Yasser Abd-Elgawwad El-Gabry; Mostafa Gamal Eldin Shahin; Sobhi Faid Lamlom; Yosri Nasr Ahmed; Ayman Farid Abou-Hadid; Shaimaa Hassan Abd-Elrahman (Horticulturae)
Applying nitrogen fertilizers in agriculture can cause uncontrolled gas emissions, such as N2O and CO2, leading to global warming and serious climate changes. In this study, we evaluated the greenhouse gas emissions (GHGs) that are concomitant with applying different rates of N fertilization, i.e., 50, 75, 100, and 125% of the recommended dose (727 kg N ha−1) for two cultivars (Balady and Sids-40) of Allium sativum L. grown under three planting dates (15 September, 1 October, and 15 October). For this purpose, two field experiments were carried out during the two growing seasons of 2020/2021 and 2021/2022. Treatments were arranged in a split–split plot design with three replicates: planting dates were set up in the main plots, nitrogen levels were conducted in the submain plots, and garlic varieties were in the sub-subplots. The obtained results can be summarized as follows: Planting on 15 September significantly increased vegetative growth parameters (i.e., plant height, leaves area, number of leaves plant−1, and leaves dry weight) and total bulb yield, in both seasons. The application of the highest rate of N (125%) gave significantly higher records for vegetative growth parameters, while the 75% nitrogen treatment appeared to give the highest total bulb yield in both seasons. The means of plant growth characteristics and total bulb yield were significantly increased by the cultivation of the Balady cultivar. In addition, the results show that GHGs were positively correlated with increasing the rate of N fertilization. It could be recommended that planting on 15 September and fertilizing with 75% N fertilizer from the recommended dose for Balady cultivar achieve maximum yield and its components.